2021
DOI: 10.1108/apjml-11-2020-0835
|View full text |Cite
|
Sign up to set email alerts
|

The impact of public policy marketing, institutional narratives and discourses on renewable energy consumption in a developing economy

Abstract: PurposeThe transition from fossil fuels to renewable energy such as solar energy is difficult and requires significant ongoing public policy marketing initiatives. Drawing on institutional theory, this paper aims to explore how public policy marketing initiatives through institutional narratives and discourses legitimize solar energy's sustainable consumption in a developing economy.Design/methodology/approachUsing a post-structuralist approach, the authors undertook a thematic analysis to study the process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…There are several usages that have been done from the non-renewable resources which have created the highest rate and make huge implications on the environment. Environmental degradation has made a huge adverse impact from past years which also lead to climate change [12]. This may bring drastic change in economic growth and companies may face high turnover for less effective revenue.…”
Section: Resultsmentioning
confidence: 99%
“…There are several usages that have been done from the non-renewable resources which have created the highest rate and make huge implications on the environment. Environmental degradation has made a huge adverse impact from past years which also lead to climate change [12]. This may bring drastic change in economic growth and companies may face high turnover for less effective revenue.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in contrast to Kagiannas et al (2003), Cheah and Low (2022), and Krishnan and Butt (2022), it has been found that the contribution to the sustainable and environmental development of energy economics is provided not through government regulation, but through the marketing of EnergyTech companies. Rethinking the activities of energy companies from the standpoint of the Noospheric approach revealed that the economic component prevails in the activities of oil and gas companies.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the contribution of energy companies to sustainable and environmental development of energy economics is determined by government regulation of their operations (Kagiannas et al, 2003). The marketing of oil and gas companies is described in detail in the works of Cheah and Low (2022) and Krishnan and Butt (2022), which note the insignificant role of marketing in ensuring the contribution of these companies to the sustainable and environmental development of energy economics.…”
Section: Noospheric Approach To Marketing Of Energytech Companiesmentioning
confidence: 99%
“…In a marketing context, hegemonic stability can also intersect with political ideology when it comes to B2B transactions. Distinctive political ideologies may support economic policies, market structures and/or regulatory frameworks, all of which have the potential to influence the subtleties of B2B dealings (Cheah and Low, 2022). For example, in a market driven by neoliberal ideology (i.e.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%